Expressions of criticality in expert and student writing: a corpus contrastive analysis of literature reviews / Muna Liyana Mohamad Tarmizi and Anealka Aziz Hussin - Mohamad Tarmizi, Muna Liyana; Aziz Hussin, Anealka (Universiti Teknologi MARA, 2021)
Literature review in academic writing plays an integral role in demonstrating writers’ knowledge about a field of study as well as in informing the influential researchers and research groups in the field. More importantly, writers are expected to critically analyze previous studies related to their topic. Despite its importance to the academic text, student writers find it challenging to establish a critical stance and to provide evaluative judgment when reviewing the literature. This paper presents a constructive analysis of expert and student writers’ expressions of criticality in literature review sections. The study first determined the types of critical expressions used by the two groups of writers and then, compared the similarities and differences of the use of criticality expressions based on Hyland’s Interactional Model of Academic Discourse. A corpus-based approach was adopted to identify the most common expressions of criticality used by these two groups of writers which were selected using a purpose sampling technique. Word Smith Tools was used to analyze the samples. The findings revealed that, unlike the expert writers, the student writers prefer to use hedges and boosters to express criticality and the evaluations sounded more like reporting rather than analyzing and synthesizing the resources critically. Results from this study are beneficial for constructing pedagogical instructions and guidelines for student writers in their critical analysis of the literature review.